2017
DOI: 10.1186/s12870-017-0977-7
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based Protein Profiling and Fruit Quality Changes at Different Development Stages of Oriental Melon

Abstract: BackgroundOriental melon is one of the most popular crops for its nutritional and flavour quality. Components that determine melon quality, such as sugar, colour, texture, flavour and aroma, among other factors, accumulate in different developmental stages. Thus, correlating the proteomic profiles with the biochemical and physiological changes occurring in the oriental melon is very important for advancing our understanding of oriental melon quality in the ripening processes.ResultsiTRAQ-based protein profilin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 91 publications
2
28
0
Order By: Relevance
“…The classification of these makuwa types of the conomon group within this aromatic cluster was not unexpected, as makuwa melons have been reported to have a specific aroma and climacteric behavior. Several recent studies reported esters, basically acetates and ethyl esters, in this sweet oriental makuwa melons, detecting ethyl acetate and hexyl acetate as the principal volatile constituents, which is in agreement with our results . Molecular results also agree with this similarity, as previous studies grouped some makuwa types with cantaloupes .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The classification of these makuwa types of the conomon group within this aromatic cluster was not unexpected, as makuwa melons have been reported to have a specific aroma and climacteric behavior. Several recent studies reported esters, basically acetates and ethyl esters, in this sweet oriental makuwa melons, detecting ethyl acetate and hexyl acetate as the principal volatile constituents, which is in agreement with our results . Molecular results also agree with this similarity, as previous studies grouped some makuwa types with cantaloupes .…”
Section: Resultssupporting
confidence: 93%
“…In fact, it has been suggested that the aroma profile is highly genotype dependent, although it also presents an environmental effect . Most studies conducted to date in melon have analyzed some genotypes of commercial interest, mainly representative of the cantaloupe or winter melon market classes, with only a few references including samples of other horticultural groups ( conomon , makuwa and dudaim ) . These previous studies have focused on specific chemical pathways or on the changes in VOC content measured with different methodologies, and under different developmental stages, postharvest conditions or crop management, including fertilization, irrigation and grafting , .…”
Section: Introductionmentioning
confidence: 99%
“…Fruit firmness is closely related to soluble pectin content, and up-regulation of UDP-glucose 6-dehydrogenase expression may thus lead to fruit softening (Fischer and Bennett, 1991 ). Expression of UDP-glucose 6-dehydrogenase was found to be increased in melon fruits at a late stage of maturation (Guo et al, 2017 ). Additional KEGG pathways, including those related to sucrose metabolism (“starch and sucrose metabolism” and “galactose metabolism”) and amino acid metabolism (“alanine, aspartate, and glutamate metabolism,” “glycine, serine, and threonine metabolism,” and “tryptophan metabolism”), were shown to be up-regulated in the fruit peels of ST persimmon (Table S6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been performed using cultivars with contrasting phenotypes for the ripening process, nonclimacteric (Inodorus group), and fully climacteric (Cantalupensis group) melons. In addition, the variability found in this trait in Asian melons (belonging to the Conomon or Makuwa groups) that have an intermediate ripening behavior (Guo et al, 2017) is also being explored (Moreno et al, 2008;Zhang et al, 2015).…”
Section: Bel En Pic Omentioning
confidence: 99%